Responsabilidade social da empresa e trabalho decente: análise do compliance à luz da policontexturalidade - Freitas, Larissa Teixeira Menezes de (2021)
This thesis deals with the corporate social responsibility and decent work through the analysis of compliance in light of polycontexturality. Referring to the historical framework of industrial relations, it should be noted that from the rude (savage) use of the labor force, without any State intervention, until the so-called postmodernity, working conditions have undergone an important evolution towards greater understanding and implementation of all protective legislation. However, there is a systemic imbalance visualized through the various crises (political, economic, social and environmental) founded on an uncontrolled and paradoxical capitalism where the Law reacts and reprograms itself. Postmodernity has erected a scenario composed of several paradoxes. As concepts such as sustainability, development and social responsibility emerged and deepened, in the same proportion and in opposite directions, serious violations of human rights, especially at work, occurred. We are currently living in a crisis scenario: economic, social, labor, environmental, among others, opening up an even darker side with regard to decency and dignity at work. On the other hand, it is worth remembering that decency at work evokes development. The concept of corporate social responsibility and compliance, bringing changes in behavior and business discourses. As concepts of corporate social responsibility are transmitted, so are business discourses, due to the need to publicize concerns about the community, sometimes as great advertising or marketing strategies, even when disrespecting fundamental rights, in practice. Corporations, in a post-modern context, are self-regulating, that is, there is a specific regulation of companies separated from the State. International law and its systems are no longer able to adequately cover the subject and they lack instruments capable of guaranteeing and enforcing human rights, especially the primacy of decent work (a key concept that will permeate the whole thesis), paradigm of the International Labor Organization (ILO). The thesis now presented takes care to face this paradoxical situation that involves the penetration of human rights in the business environment, based on regimes of private regulation of economic activity. To this end, the theory of systems was chosen as a theoretical framework, along the lines designed by Niklas Luhmann, enriched with the contributions of Gunther Teubner, about the legal phenomenon as a reticulated heterarchy and endowed with poly-contextuality. The objective is to analyze from the perspective of polycontexturality, how private regulatory regimes implemented in companies under the notion of corporate social responsibility, especially compliance, impact on the effectiveness of fundamental labor rights, taking into account decent work as a conducting link. This is a research that uses systems theory as a method of approach, with the theoretical framework of the works of Gunther Teubner, applying constitutional hermeneutics to assess the hypothesis, based on the analysis of legal and jurisprudential texts.